Motivational bases for consumers' underdog affection in commerce. (19th June 2017) - McGinnis, Lee Phillip; Gao, Tao; Jun, Sunkyu; Gentry, James
Abstract : Purpose: The understanding of the motives for consumers' support of business underdogs is generally limited. The purpose of this paper is to help address this important research topic by conceptualizing underdog affection as a theoretical construct capturing the emotional attachment held by some consumers toward underdog business entities and advances two perspectives (self- and other-oriented) to unravel its motivational underpinnings. Design/methodology/approach: To test the conceptual model, a survey study was conducted involving 365 respondents drawn from an electronic alumni association list from a medium-sized Midwestern university in the USA. Exploratory factor analysis and confirmatory factor analyses were used to validate the scales, and the structural equations modeling method was used to test the hypothesized effects. Findings: The data support most of the hypotheses (eight out of nine). Under the self-oriented perspective, commerce underdog affection is positively influenced by underdog orientation, need for uniqueness, nostalgia proneness, and hope, and is negatively impacted by their materialism level. Only hope did not impact consumer underdog affection. Under the other-oriented perspective, balance maintenance, top dog antipathy, and empathic concern positively influence underdog affection. The other-oriented factors, especially top dog antipathy and balance maintenance, show stronger effects on commerce underdog affection than self-oriented factors. Research limitations/implications: The sample was geographically restrictive in the sense that it measured only one group of respondents in the USA. The conceptual model is limited in terms of its coverage of the consequences of underdog affection. While discriminant validity is established in the scale development phase of the study, relatively close relationships do exist among some of these theoretical constructs. Practical implications: Given the significant evidence linking consumers' underdog affection to underdog support in commerce, small locally owned businesses could use underdog positioning advertising to differentiate themselves against national retailers. Due to their tendency to display higher underdog affection in commerce, people with higher levels of balance maintenance, top dog antipathy, underdog orientation, emphatic concern, and nostalgia proneness, and lower levels of materialism can be segmented for marketing purposes. Social implications: This research indicates that there are ways in which small business entities and non-profits alike can operate in a business setting that is increasingly more competitive and challenging for underdog entities. Originality/value: This study integrates the various underdog studies across contexts to examine motives to underdog affection, a construct not yet operationalized in business studies. In addition, hypotheses linking eight specific antecedents to commerce underdog affection, via two theoretical perspectives, are empirically examined to assess relative as well as absolute effects.